2014
DOI: 10.1364/boe.5.003238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic effects on Pseudomonas aeruginosa biofilm using Raman spectroscopy and multivariate analysis

Abstract: Abstract:We investigate the mode of action and classification of antibiotic agents (ceftazidime, patulin, and epigallocatechin gallate; EGCG) on Pseudomonas aeruginosa (P. aeruginosa) biofilm using Raman spectroscopy with multivariate analysis, including support vector machine (SVM) and principal component analysis (PCA). This method allows for quantitative, label-free, non-invasive and rapid monitoring of biochemical changes in complex biofilm matrices with high sensitivity and specificity. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 50 publications
3
57
0
Order By: Relevance
“…Some of these include the evaluation of antibiotic treatments [488], identification of circulating tumor cells [489], and classification of inflammatory bowel disease [490]. Stöckel et al used a hierarchy of SVM and LDA classifiers to identify bacterial species [491].…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…Some of these include the evaluation of antibiotic treatments [488], identification of circulating tumor cells [489], and classification of inflammatory bowel disease [490]. Stöckel et al used a hierarchy of SVM and LDA classifiers to identify bacterial species [491].…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…The effects of antibiotics on Pseudomonas aeruginosa biofilms have also been shown [46]. Biofilms grown in a microfluidic device were monitored with CLSM and their composition was characterized by Raman spectroscopy in the presence of three antibiotics (ceftazidime, patulin, and epigallocatechin gallate; EGCG).…”
Section: Raman Spectroscopy Of Biofilmsmentioning
confidence: 99%
“…Such rapid, nondestructive, label‐free analysis has been used effectively in real‐time monitoring of subtle cellular changes. We previously investigated microstructural and biochemical changes in tissues from in vivo and in vitro human and animal studies detected by Raman spectroscopy (Ahn et al, ; Choi et al, ; Jung et al, ; Kim et al, ; Lee et al, ; Shin et al, ). Our results showed that distinctive Raman peaks were observed in different treatment methods and tissues and could be used as biomarkers to detect abnormalities.…”
Section: Discussionmentioning
confidence: 99%